PUBLIC SPEAKING STRATEGIES OF WOMEN FIGURES IN BUILDING PUBLIC CREDIBILITY AND TRUST: A CASE STUDY OF NAJWA SHIHAB, SRI MULYANI INDRAWATI, AND RETNO MARSUDI IN THE DIGITAL ERA (2020–2025) - Amalia Azmi Sitorus; Afni Yoana Tjahyani Gusma; Fahmi Hasan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study specifically examines how the public speaking strategies used by three Indonesian female figures, Najwa Shihab, Sri Mulyani Indrawati, and Retno Marsudi, generated strong credibility and public trust in different communication domains during the period 2020–2025. Using an instrumental qualitative case study approach with cross-case analysis, this study analyzed 47 documented public communication events including 18 interview episodes (Najwa Shihab), 16 press conferences and policy speeches (Sri Mulyani Indrawati), and 13 diplomatic speeches (Retno Marsudi) triangulated with academic literature and public trust survey data. Based on Source Credibility Theory (Hovland & Weiss, 1951; McCroskey, 2006), Narrative Paradigm (Fisher, 1984), and Authentic Leadership Communication (Northouse, 2021), this study found that the effectiveness of female public speaking in building credibility and public trust is determined by four pillars that work integratively: (1) demonstrated professional competence, (2) consistent communication that builds integrity, (3) social empathy that creates emotional resonance, and (4) authenticity that strengthens value trust. Based on the synthesis of findings, this study proposes the PSCT Framework (Public Speaking Credibility Trust) as a conceptual model that explains credibility as a mediating variable between public speaking strategies and the formation of sustainable public trust, with moderating factors of gender and the digital media environment.